The Donner Party - Werther, Scott P. (New York : Children's Press, 2002)
Describes the journey of the ill-fated Donner Party, ninety pioneers who became stranded in the Sierra Nevada mountains in the winter of 1846-47.
Includes bibliographical references (p. 44) and index.
Keywords: Donner Party -- Juvenile literature; Pioneers -- California -- Biography -- Juvenile literature; Donner Party; Pioneers; Overland journeys to the Pacific; Survival